A Novel Anti-EGFR mAb Ame55 with Lower Toxicity and Better Efficacy than Cetuximab When Combined with Irinotecan. (13th January 2019) - Qiu, Weiyi; Zhang, Chang; Wang, Shuang; Yu, Xiaoyan; Wang, Qiong; Zeng, Dadi; Du, Peng; Ma, Jinling; Zheng, Yiqiong; Pang, Bo; Yu, Yunzhou; Long, Feng; et al.
Abstract : To improve efficacy and minimize toxicity of EGFR inhibition treatment, we developed Ame55, a novel anti-EGFR IgG1 with lower affinity to EGFR than cetuximab (C225) from a human phage library. Ame55 had lower bioactivity than cetuximab in vitro but similar antitumor efficacy as cetuximab in vivo . Moreover, Ame55 was more efficacious than cetuximab in a Lovo cell xenograft tumor model when combined with irinotecan (CPT-11). Ame55 concentrates in the mouse xenograft tumor and has less toxicity than cetuximab in cynomolgus monkeys in an overdose study.